(untitled) (Bangladesh Journal of Zoology, 2012)
The study was an initiative to assess the impacts of training supports under aquaculture extension activities provided to the female farmers involved in pond fish culture in comparison to the male farmers from different areas of Bangladesh. It is also identified that constraining factors affect the participation of female farmers in fish culture after receiving training supports under aquaculture extension program. The mean baseline fish production by the female farmers was 3.8 ± 1.2 kg/dec and after getting training supports it increased to 6.8 ± 2.1 kg/dec, which was significantly (p < 0.001) higher (78%) in comparison to their baseline. Overall, there was increased fish production in the ponds of the trained female farmers in comparison to their baseline year (before trained) fish production in ponds; however, their fish production was lower than that of the male farmers who received the similar sort of supports. Different factors were related to the low level of involvement of females in fish culture and the low level of fish production was related to households, social and cultural reasons. Females were busy in managing usual household works especially taking care of their children and having limited time to make regular contact with extension officers. Low level of literacy, socio-cultural barriers, higher dependency on their male counterparts, their less ability to take decision, and comparatively their poor health condition are factor constraints for their active involvement in aquaculture. DOI: http://dx.doi.org/10.3329/bjz.v39i2.10591 Bangladesh J. Zool. 39(2): 213-221, 2011